2013
DOI: 10.1128/genomea.00260-13
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Salmonella enterica Serotype Tennessee Strain CDC07-0191, Implicated in the 2006-2007 Multistate Food-Borne Outbreak Linked to Peanut Butter in the United States

Abstract: Salmonella enterica serotype Tennessee strain CDC07-0191 was isolated from the 2006-2007 multistate food-borne outbreak linked to peanut butter in the United States. Here we report a high-quality draft assembly of the genome sequence of this strain, derived from a patient. This is the first reported high-quality draft genome sequence for S. enterica serotype Tennessee, which will enable in-depth studies of its transmission and virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The 2014 outbreak exemplifies the public health challenges posed by multi-national disease outbreaks ( Chatt et al, 2017 ; Deng et al, 2013 ; Kinross et al, 2014 ) that are a consequence of the widespread trade of food and other goods across borders ( van Belkum et al, 2007 ). Such outbreaks present difficulties in their detection, description, and resolution, as most disease surveillance occurs at the national level ( van Belkum et al, 2007 ), which makes the uniform characterisation of disease-associated isolates in different jurisdictions essential.…”
Section: Introductionmentioning
confidence: 99%
“…The 2014 outbreak exemplifies the public health challenges posed by multi-national disease outbreaks ( Chatt et al, 2017 ; Deng et al, 2013 ; Kinross et al, 2014 ) that are a consequence of the widespread trade of food and other goods across borders ( van Belkum et al, 2007 ). Such outbreaks present difficulties in their detection, description, and resolution, as most disease surveillance occurs at the national level ( van Belkum et al, 2007 ), which makes the uniform characterisation of disease-associated isolates in different jurisdictions essential.…”
Section: Introductionmentioning
confidence: 99%
“…Other outbreaks were associated with peanut-containing snacks in Israel and North American (Killalea et al, 1996) and Asian-style peanuts still in their shell (Kirk et al, 2004). From 2006 to 2007, Salmonella Tennessee in peanut butter was responsible for a major food-borne disease outbreak in the United States (Deng et al, 2013;MMWR, 2007). An epidemiological study identified 715 cases from 48 states, resulting in 93 hospitalizations (Sheth et al, 2011).…”
mentioning
confidence: 99%